Factors of fraud intention among public officials in Kelantan / Azelina Ismail @ Hassan - Ismail @ Hassan, Azelina (2023)
Fraud has permeated both the corporate and public sectors worldwide, tainting the image and reputation of the countries. The Malaysian public sector is one of the emerging economies that has been plagued with the issue of fraud. Since the public sector was funded by the public fund, the taxpayers and public expect the fund to be spent for the interest and benefits of all Malaysians. Indeed, it would be a waste of resource if the allocations for government expenditure were abused for fraudulent or unlawful activities. Moreover, the government appoints public officials to look after the public interests. However, the involvement of several public officials in fraudulent activities have raised a concern on the factors that lead them to commit fraud. This phenomenon has triggered the researcher to investigate the factors of fraudulent intention among public officials in Kelantan. Following Fraud Triangle Theory, the researcher predicts that fraud intention is related to opportunity, stress and rationalization. A total of 250 questionnaires were distributed to public officials in finance division of federal agencies in Kelantan. Employing SPSS 27, the findings reveal that all the three factors which are pressure, opportunity and rationalization have significant positive relationships with fraud intention. The discoveries of the study are useful for policy makers, academicians, public officials and the public at large to enhance existing control mechanism in fraud prevention activities. The study concluded that government needs to enhance fraud awareness through social media and training programs, besides imposing stricter enforcement to combat fraud incidences as fraud should be fought in all forms.